2004
DOI: 10.1016/s0014-5793(03)01494-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial small heat‐shock protein enhances thermotolerance in tobacco plants

Abstract: To clarify the role of mitochondrial small heat-shock protein (MT-sHSP) in the heat-shock response, we introduced the tomato (Lycopersicon esculentum) MT-sHSP gene under the control of the 35S promoter into tobacco (Nicotiana tabacum), and examined the thermotolerance of the transformed plants. Irrespective of the orientation, sense or antisense, of the gene, the transgenic plants exhibited a normal morphology and growth rate in the vegetative growth stage. When 4-weekold seedlings were exposed to sudden heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 34 publications
(34 reference statements)
1
89
0
2
Order By: Relevance
“…Along with our results, Yeh and coworkers [35] also reported that the overexpression of sHSPs in E. coli showed enhance thermotolerance, as well as changes in the protein aggregation patterns. In addition, it has also been reported that the overexpression of a tomato Mt sHSP raised the thermotolerance of transgenic tobacco plants [8]. Together with these reports, the current results provide a clear indication that sHSPs play an important role in plant-acquired heat stress tolerance [13].…”
Section: Hspssupporting
confidence: 81%
See 1 more Smart Citation
“…Along with our results, Yeh and coworkers [35] also reported that the overexpression of sHSPs in E. coli showed enhance thermotolerance, as well as changes in the protein aggregation patterns. In addition, it has also been reported that the overexpression of a tomato Mt sHSP raised the thermotolerance of transgenic tobacco plants [8]. Together with these reports, the current results provide a clear indication that sHSPs play an important role in plant-acquired heat stress tolerance [13].…”
Section: Hspssupporting
confidence: 81%
“…Recently, several efforts have been taken to produce enhanced heat-tolerant plants through genetic transformation [6][7][8]. The identification of novel genes, which determines their expression patterns in response to stress and in understanding their functions in stress adaptation, will provide the basis for effective strategies in improving stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The development and survival of plants is constantly challenged by changes in environmental conditions. To overcome adverse conditions, plants elicit complex physiological and molecular responses, activating a large set of genes leading to the accumulation of specific Designations of functional categories: A RNA processing and modification, B chromatin structure and dynamics, C energy production and conversion, D cell-cycle control and mitosis, E amino acid metabolism and transport, F nucleotide metabolism and transport, G carbohydrate metabolism and transport, H coenzyme metabolism, I lipid metabolism, J translation, K transcription, L replication and repair, O post-translational modification, protein turnover, chaperone functions, P inorganic ion transport and metabolism, Q secondary metabolites biosynthesis, transport and catabolism, R general functional prediction only, S function unknown, T signal transduction, U intracellular trafficking and secretion, Z cytoskeleton, * non-conclusive stress-associated proteins, such as HSPs (Borges et al 2001;Sanmiya et al 2004). Although there is a general decrease in the synthesis of many constitutively expressed proteins in a stressed situation, the translation machinery remains active and the synthesis of several HSPs is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…The ER, P, M, and Po sHsps have all been localized in vivo to the respective organelles and cannot be detected in the cytoplasm. Mitochondrial sHsps are reported to be involved with the protection of mitochondrial proteins during hs and with increased thermotolerance (Chou et al 1989;Liu and Shono 1999;Sanmiya et al 2004). Similarly, overexpression of the chloroplast-localized sHsp protects photosystem II under some stress conditions (Neta-Sharir et al 2005;Guo et al 2007).…”
Section: Introductionmentioning
confidence: 99%